A National Biodiversity Offset Scheme : A Road Map for Liberia’s Mining Sector - World Bank Group (World Bank, Washington, DC, 2015)
Liberia had an estimated 4.3 million hectares of forests in 2011, comprising approximately 50 percent of Liberia’s landmass. These forests support very high levels of biodiversity, provide a wide range of ecosystem services (for example, bush meat, medicines, construction materials, and charcoal), and generate employment and revenue from commercial and chainsaw logging. Encouraging inward investment while striking a sound balance between different interests, respecting the legal and customary rights of local people, and conserving biodiversity represents a major challenge. This project focuses on the mining sector, which has the potential to become a significant engine for growth and broader-based development. It explores the feasibility of implementing a national biodiversity offset scheme in Liberia to help minimize adverse impacts on biodiversity and ecosystem services resulting from mining. A Liberian national offset scheme will entail the application of a common methodology to ensure that conservation benefits are at least equivalent to biodiversity losses due to mining investments. The report is presented in seven chapters. Chapter one gives introduction. Chapter two discusses the conservation imperatives for Liberia and conveys a sense of the quality and extent of biodiversity within Liberia. Chapter three describes the challenge of securing conservation outcomes in Liberia as well as the prevalence of threats to biodiversity. Chapter four discusses the potential for biodiversity offsets to help secure conservation outcomes. Chapter five covers the legal, policy, and institutional framework in support of biodiversity offsets. Chapter six discusses the methodological aspects of implementing a national biodiversity offset scheme, together with the challenges of securing and effectively managing sources of funding. Chapter seven summarizes the report’s suggested next steps to implement a road map for biodiversity offsets in Liberia.